Pengaruh Komunikasi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan UD Tenun Ikat Kodok Ngorek - Della Ayu Puspita; Rafikhein Novia Ayuanti (Jurnal Publikasi Ilmu Manajemen, 2022)
The purpose of this study is to determine and explain whether there is an influence between the variables of communication, work discipline and work environment on the performance of UD Tenun Ikat Kodok Ngorek employees. Several factors including communication, work discipline and work environment at UD Kodok Ngorek have an influence on employee performance using the sampling method with a saturated sampling approach. The data analysis technique is using the instrument test of validity and reliability, multiple linear test, classical assumption test, t test and F test of the coefficient of determination (R2). The number of samples is 30 employees. The results obtained include a partially significant effect of communication on work performance with the value of Sig. 0.000 < 0.05. The partial effect of work discipline on employee performance has a value of Sig. 0.037 <0.05 which means that it has a significant effect then the influence of the work environment on employee performance partially also has a significant effect on the value of Sig. 0.002 < 0.05. The simultaneous influence of the variables of communication, work discipline and work environment on employee performance has a Sig value result. 0.000 <0.05 indicates that communication, work discipline, and work environment have a positive influence in improving employee performance at UD Tenun Ikat Kodok Ngorek.